Network virtualization over elastic optical networks with different protection schemes - Assis, K. D. R.; Peng, S.; Almeida, R. C.; Waldman, H.; Hammad, A.; Santos, A. F.; Simeonidou, D. (Journal of optical communications and networking, 2016)
With network virtualization, the physical infrastructure can be partitioned into multiple parallel virtual networks for sharing purposes. However, different transport technologies or quality of service (QoS) levels may impact both the requested amount of resources and the characteristics of different virtual instances that can be built on top of a single physical infrastructure. In this paper we propose a novel mixed integer linear programming (MILP) formulation for different schemes of protection in scenarios where multiple virtual topologies run over an elastic optical network. The proposed MILP formulation uses the concept of bandwidth squeezing to guarantee a minimum bandwidth for surviving virtual topologies. It achieves a high level of survivability for traffic that is subject to a different committed service profile for each virtual topology. Case studies are carried out in order to analyze the basic properties of the formulation in small networks, and three heuristics are proposed for larger networks.